(untitled) (Research, Society and Development, 2022)
Bioethical principles in academic-scientific studies were knowledge developed in the middle of the last century, this considering it something very recent, especially of paramount importance in studies involving human beings and animals in the fields of clinical and social research. Objective: to describe the critical review of the film “Spiderhead”, under the aegis of the principles of bioethics in research. Methodological Approach: A critical review study, developed during the Bioethics course, of the Graduate Program in Nursing – Master’s at the Federal University of Alagoas. Results: The synopsis of Spiderhead brings a science fiction set in a conceptual penitentiary called, located on an island far from civilization, testing formulas on people who should have gone to jail, but were stuck on the island for such experiments, which led to reflection on bioethical principles: autonomy, justice, beneficence and non-maleficence. Final considerations: In this way, analyzing the movie “Spiderhead”, under the aegis of the principles of bioethics in research, it is possible to apprehend that all mandatory steps for the process of experimenting with human beings were violated. Participants were unaware of the nature of the research, the drugs they used and the risks they ran, verbally authorizing their participation and being constantly coerced into remaining.